Activation of RyR2 by class I kinase inhibitors - Chakraborty, A. D. (2018)
Background and Purpose: Kinase inhibitors are a common treatment for cancer. Class I kinase inhibitors that target the ATP-binding pocket are particularly prevalent. Many of these compounds are cardiotoxic and can cause arrhythmias. Spontaneous release of Ca2+ via cardiac ryanodine receptors (RyR2), through a process termed store overload-induced Ca2+ release (SOICR), is a common mechanism underlying arrhythmia. We explored whether class I kinase inhibitors could modify the activity of RyR2 and trigger SOICR to determine if this contributes to the cardiotoxic nature of these compounds. Experimental Approach: The impact of class I and II kinase inhibitors on SOICR was studied in HEK293 cells and ventricular myocytes using single-cell Ca2+ imaging. A specific effect on RyR2 was confirmed using single channel recordings. Ventricular myocytes were also used to determine if drug-induced changes in SOICR could be reversed using anti-SOICR agents. Key Results: Class I kinase inhibitors increased the propensity of SOICR. Single channel recording showed that this was due to a specific effect on RyR2. Class II kinase inhibitors decreased the activity of RyR2 at the single channel level but had little effect on SOICR. The promotion of SOICR mediated by class I kinase inhibitors could be reversed using the anti-SOICR agent VK-II-86. Conclusions and Implications: Part of the cardiotoxicity of class I kinase inhibitors can be assigned to their effect on RyR2 and increase in SOICR. Compounds with anti-SOICR activity may represent an improved treatment option for patients.